Strongyloidiasis in dogs: A case report - Silvestrini, Angela (Pubvet, 2022)
The contemporary relationship between humans and animals in the environment that surrounds them increases the chance of occurrence and transmission of zoonosis. Strongyloidiasis is a worldwide zoonotic disease that can affect humans and animals, especially dogs, and its etiological agent is Strongyloides sp. This paper presents a case report in a young dog acquired from a commercial kennel, which was delivered to new tutors without proper parasitic control, showing signs of apathy, hyporexia, vomiting and mucus-filled feces. From the exams performed, a parasitic infection by S. stercoralis was identified, promptly treated with antiparasitic drugs.
Keywords: Strongyloidiasis; zoonosis; one health